2020
DOI: 10.3126/forestry.v17i0.33624
|View full text |Cite
|
Sign up to set email alerts
|

Avifaunal Diversity of Institute of Forestry Complex, Hetauda Metropolis, Nepal

Abstract: Avifaunal diversity is the measure of species diversity via species richness and evenness. To this aim, avifaunal survey was conducted in the Institute of Forestry Complex, Hetauda from November 2017 to June 2018. Using line transect and point count methods, 132 species of birds were recorded, representing 15 orders and 44 families. Three species of these birds are in IUCN Red List while 90, 27 and 15 species are residential, visitor and migrant respectively. Higher Shannon diversity index (4.47) and Margalef … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
1
3
1
Order By: Relevance
“…Moreover, higher bird diversity in Changunarayan might be due to the presence of many ponds, abundant food sources such as fishes, aquatic plants, planktons, invertebrates and suitable habitat for breeding. Nevertheless, our result contradicts with the findings made by Bhusal et al (2021) and Bajagain et al (2020) where a greater variety of species was reported in the Machhapalan complex than in Institute of Forestry complex despite being relatively small in area coverage.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Moreover, higher bird diversity in Changunarayan might be due to the presence of many ponds, abundant food sources such as fishes, aquatic plants, planktons, invertebrates and suitable habitat for breeding. Nevertheless, our result contradicts with the findings made by Bhusal et al (2021) and Bajagain et al (2020) where a greater variety of species was reported in the Machhapalan complex than in Institute of Forestry complex despite being relatively small in area coverage.…”
Section: Discussioncontrasting
confidence: 99%
“…These results also align with a study in Machhapalan Complex, Hetauda (Bhusal et al 2021). In contrast to our study, the highest number of species was reported under the Corvidae family in the study made by Bajagain et al (2020) and Chaudhari et al (2009). The reason behind the Muscicapidae found as the most diverse family might be because of being one of the largest bird families with great variability in morphology and behavior (Zhao et al 2023) where they have clearly stated that none of the threatened species recorded in the areas falls under the protected bird species list of Nepal.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Most of them are carried out in community forests while studies on national forests is lacking. The forest area of IoF supports 98 species of butterflies (Chhetri, 2017), 91 species of birds (Pokharel, 2017), and 11 species of snakes (Pradhan et al, 2020) and a population of spotted deer (Axis axis) (Bhusal et al, 2020). The study area is surrounded by human settlements on the north, east, and south sides, highlighting the urgent need for conservation intervention (Bajgain et al, 2020).…”
Section: Introductionmentioning
confidence: 93%